Pengaruh Citra Merek, Kualitas Produk, dan Persepsi Harga terhadap Keputusan Pembelian di Bakso Boedjangan Juanda Bekasi - Bella Riska Putri Edyanto; Chatarina Yunita (LPPM Universitas Asa Indonesia, 2022)
This study aims to determine and analyze the effect of brand image, product quality, and price perception on purchasing decisions at Bakso Boedjangan Juanda Bekasi. The population in this study was 100 respondents with data collection using a questionnaire given to respondents with accidental sampling technique. The analytical method used in this research is multiple regression analysis. The results of this study indicate that brand image variables, product quality variables, and price perception variables simultaneously influence purchasing decisions at Bakso Boedjangan Juanda Bekasi. Then the partial results show that the product quality and price perception variables have a significant effect on purchasing decisions while the brand image variable has no effect on purchasing decisions,